Preparation method and application of bone repair scaffold
By introducing titanium dioxide into the calcium silicate bone repair stent, the problems of insufficient mechanical strength and rapid degradation of existing bone repair materials were solved, and the biological activity and mechanical properties of the bone repair stent were significantly improved, which promoted the rapid repair of bone defects.
Patent Information
- Application Number
- CN202411933871.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-18
AI Technical Summary
The existing bone repair materials are insufficient mechanical strength, fragile and degraded too quickly, making it difficult to effectively promote bone regeneration and angiogenesis.
Titanium dioxide is introduced into the calcium silicate bone repair scaffold, and bone repair scaffolds with enhanced biological activity and improved mechanical properties are prepared by mixing powder, printing slurry, 3D printing and sintering.
It significantly enhances the biological activity and mechanical properties of the bone repair stent, delays the degradation rate, and accelerates the repair process of bone defects.
Smart Images

Figure CN119838053A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a preparation method and application of a bone repair scaffold. Background Art
[0002] Bone is one of the most important organs in the human body. It is responsible for protecting other organs, producing blood cells, and regulating the body's functions. It is mainly composed of matrix and mineral phase. The matrix includes proteins such as collagen, proteoglycans and lipids, and the mineral phase is mainly hydroxyapatite. At present, a variety of orthopedic diseases including bone defects and osteoporosis have caused huge economic and health care problems around the world. Traditional methods for repairing bone defects include bone transfer technology, membrane induction technology and bone transplantation, but these methods have symptoms such as long treatment cycles, nail infection, bone nonunion, and due to limited bone supply, there are also risks such as bone infection. Bone tissue engineering aims to use three-dimensional biodegradable scaffolds combined with bone marrow stem cells or mesenchymal stem cells to accelerate tissue regeneration and reconstruction with bioactive signals such as growth factors. Bone scaffold construction plays a vital role in simulating the extracellular matrix of natural bone, providing support and inducing tissue regeneration through ion release and cell proliferation, differentiation, and accelerating bone tissue regeneration. Bone scaffold implants need to be functional, non-toxic, non-teratogenic, biocompatible, non-immunogenic, and must consistently exhibit appropriate mechanical and physicochemical properties, provide a microporous environment for cell growth, and facilitate nutrient transport.
[0003] Since the 1960s and 1970s, bone repair materials have gone through three generations of development. The first generation of bone repair materials represented by stainless steel, titanium alloy, and zirconium oxide can only play a simple mechanical support role after being implanted in the body. Moreover, these materials have high mechanical properties and are prone to stress shielding. They will only passively adapt to the internal environment of the human body after being implanted in the human body. The materials themselves have no effect on tissue regeneration and healing. In the 1980s, bioactive materials represented by hydroxyapatite and biodegradable materials represented by degradable biopolymers appeared. With the introduction of the concepts of "bioactivity" and "degradability", researchers have been using various methods such as ion implantation and surface modification to obtain more satisfactory bone repair filling scaffolds. The concept of the third generation of biomaterials was proposed in the early 21st century. The third generation of biomaterials not only has excellent bioactivity but also takes into account degradable properties. During the degradation process, it can release a variety of ions that are beneficial to tissue repair and promote the growth and proliferation of tissue cells. At the same time, the material can be completely degraded in the body and excreted with sweat, urine, etc. In the field of bone defect repair, degradable bioactive ceramic materials such as the calcium-silicon series and calcium-phosphate series are outstanding representatives of the third generation of bioactive materials.
[0004] For calcium silicate bioactive ceramics, Ca 2+It can enhance the proliferation and differentiation of osteoblasts and osteoclasts, regulate osteogenesis by promoting angiogenesis in bone defects, promote the release of growth factors, increase bone density, inhibit osteoporosis, and enhance cell proliferation and bone mineralization. 4+ It is a bioactive component in the human body that can promote the osteogenic differentiation of bone marrow mesenchymal stem cells and participate in the mineralization process of early new bone formation, thus proving the potential of calcium silicate bioceramics to enhance osteogenesis and promote bone regeneration. Although silicate ceramic materials have many advantages, pure silicate ceramics have low mechanical strength, too fast ion release, poor chemical stability, and the high local pH value caused by them will cause certain cell discomfort. Summary of the invention
[0005] Based on the above reasons, the present application discloses a bone repair scaffold and a preparation method thereof. By introducing titanium dioxide into a calcium silicate bone repair scaffold, the prepared bone repair scaffold can significantly enhance biological activity, accelerate angiogenesis and bone regeneration, and effectively control the degradation rate of the material, improve its mechanical properties, and accelerate the repair of bone defects.
[0006] To this end, the technical solution of the present application provides a method for preparing a bone repair scaffold, comprising the following steps:
[0007] Mixing calcium silicate powder and titanium dioxide powder to obtain a mixed powder;
[0008] Adding photosensitive resin to the mixed powder to obtain printing slurry;
[0009] The printing slurry is 3D printed to obtain a printing bracket;
[0010] The printed scaffold is sintered to obtain a bone repair scaffold.
[0011] Furthermore, the added amount of the titanium dioxide powder accounts for ≤50% of the total mass of the mixed powder.
[0012] Furthermore, the added amount of the titanium dioxide powder accounts for 10% of the total mass of the mixed powder.
[0013] Furthermore, the mixed powder is added in an amount such that the solid content in the printing slurry is 30%-40%.
[0014] The specific calculation method of this process is: take the mass of the mixed powder as m, V1=m / ρ (powder density), V2 is the volume of the photosensitive resin used, and the solid content in the printing slurry=V1 / (V1+V2).
[0015] Furthermore, the sintering temperature is 1100° C.-1200° C., and the sintering time is 3 h-4 h.
[0016] Furthermore, after the sintering is completed, a drying step is also included, and the drying temperature is 50°C-60°C.
[0017] Furthermore, the bone repair scaffold prepared according to the above preparation method is used as a repair scaffold material for treating bone defects.
[0018] The beneficial effects of the present invention are as follows: titanium dioxide is added to the bone repair scaffold in the present application, which, on the one hand, can improve the problems of insufficient mechanical strength, fragility and rapid degradation of single ceramic materials in the prior art, and increase the functionality of the ceramic material; on the other hand, titanium dioxide itself has significant biological activity, can actively induce the deposition of hydroxyapatite, and promote bone integration. The Si ions released from calcium silicate can produce a unique synergistic effect with other external stimuli with biological activity (including inorganic ions, growth factors, micro-nano-Tob structures, etc.), greatly enhancing the biological activity of the Si ions themselves and other external stimuli, and further promoting angiogenesis and bone regeneration. The dual effects of the two materials provide more powerful support for the repair of bone defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Characterization pictures of bone repair scaffolds, including (a) SEM characterization of micromorphology (b) XRD characterization (c) FT-IR characterization (d) porosity (e) compressive strength (f) degradation.
[0020] Figure 2 Figure 3 Effects of bone repair scaffolds on BMSCs proliferation and differentiation, including (a, b) BMSCs proliferation after 1, 3, and 5 days of culture, (c) representative images of cell migration and (e) quantitative analysis of cell migration rate after 24 hours of culture, and (d) live-dead staining to determine the live and dead status of BMSCs, AM represents live cells (green) and PI represents dead cells (red). DETAILED DESCRIPTION
[0021] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0022] The embodiment of the present application discloses a method for preparing a bone repair scaffold, comprising the following steps: mixing calcium silicate powder and titanium dioxide powder to obtain a mixed powder; adding a photosensitive resin to the mixed powder to obtain a printing slurry; 3D printing the printing slurry to obtain a printed scaffold; and sintering the printed scaffold to obtain a bone repair scaffold.
[0023] In this embodiment, the photosensitive resin is preferably hexanediol diacrylate (HDDA), butyl acrylate (BA) and tripropylene glycol diacrylate (TPGDA), etc., the added amount of the titanium dioxide powder accounts for ≤50% of the total mass of the mixed powder; the added amount of the mixed powder is such that the solid content in the printing slurry is 40%. The specific calculation method of the process is: take the mass of the mixed powder as m, V1=m / ρ (powder density), V2 is the volume of the photosensitive resin, and the solid content in the printing slurry=V1 / (V1+V2).
[0024] In this embodiment, the 3D printing uses a 3D printer to perform general printing according to a set printing pattern.
[0025] Example 1 Preparation of bone repair scaffold
[0026] S1. Calcium silicate powder (Huaqiao Technology New Materials) and titanium dioxide powder (Shanghai Aladdin Biochemical Technology) were mixed (titanium dioxide accounted for 0, 10, 30, and 50% of the total mass of the powder, and were named CS, CST 9:1, CST 7:3, and CST 5:5, respectively) to obtain a mixed powder.
[0027] S2. The mixed powder and the photosensitive resin (hexanediol diacrylate (HDDA) (Shanghai Guoyao)) were fully stirred until there were no obvious particles and the slurry was fluid to obtain a printing slurry;
[0028] S3. The printing slurry is 3D printed. The printing process of the printer is divided into four steps: a. The scraper moves back and forth to spread the material. b. The molding table descends to the set height. c. The light machine is exposed. d. The molding table rises. These four steps are repeated until the printing is completed. After the printing is completed, the bracket is slowly removed from the molding table with a knife, and then the residual slurry inside the bracket is rinsed with a water flosser to obtain the printed bracket.
[0029] S4. Place the printed scaffold in a sintering furnace, set the sintering temperature to 1200°C, and set the sintering time to 3 hours. After sintering, rinse the scaffold and dry it in an oven at 60°C to obtain a bone repair scaffold.
[0030] Experimental Example 1 Bone repair scaffold characterization experiment
[0031] The components of the stent prepared in Example 1 were characterized using an X-ray diffractometer at 40 kV and 40 mA, respectively. The bonding composition of the stent was determined using a Fourier infrared measuring device, and the structure and surface morphology of the stent were examined using a scanning electron microscope. The mechanical properties of the stent were evaluated using a universal mechanical testing machine. The porosity of the stent was determined using the drainage method. In short, the weight of the stent was measured in the dry (M1), water-filled (M2) and water-immersed (M3) conditions.
[0032] The porosity (P) of the scaffold was calculated by the following formula: P = (M2-M1) / (M2-M3)*100%.
[0033] For the degradation experiment, the scaffold was placed in TRISHCL hydrochloride buffer solution at a ratio of 50 ml / g. The scaffold was taken out at different time points, dried at 120°C for 12 hours and weighed, and the percentage of scaffold weight loss during different immersion cycles was calculated.
[0034] Preparation of ion extract: After the prepared scaffold is sterilized by high temperature and high pressure, 10 ml of DMEM high glucose medium is added per gram of scaffold, and the scaffold is placed in a constant temperature shaker at 37°C and shaken at 150 rpm / min for 24 hours. After 24 hours of extraction, the high glucose medium extract is filtered and sterilized using a polyethersulfone (PES) filter device.
[0035] The test results are as follows Figure 1 As shown: Figure 1 (a) is the SEM characterization of the scaffold obtained in Example 1. It can be seen that with the addition of titanium dioxide, the composite ceramic scaffold gradually turns yellow, among which the CST5:5 scaffold is the most obvious. The SEM image shows that the line structure of each layer of the bone repair scaffold presents a 60° staggered structure, and all have a uniform porous structure, presenting a three-dimensional 3D interconnected structure, and there are irregular protrusions on the surface of the scaffold, making the surface structure more rough.
[0036] Figure 1 (b) is the XRD test result of the bracket obtained in Example 1, showing that a new crystalline phase CaTISIO5 (PDF#25-0177) is formed after the calcium silicate and titanium dioxide are mixed, printed and sintered, and the corresponding crystalline peak intensity increases with the increase of titanium dioxide addition.
[0037] Figure 1 (c) is the Fourier transform infrared spectroscopy (FT-IR) characterization of the scaffold obtained in Example 1, showing that the CS scaffold (without titanium dioxide) has a peak at 565 cm -1 The absorption peak is the bending vibration absorption peak of O-SI-O, 711cm -1 The SI-O-SI bending vibration absorption peak is at 981 cm -1 The SI-O stretching vibration absorption peak is at 472 cm. -1 The TI-O absorption peak appears ( Figure 1 c).
[0038] Figure 1(d) is the porosity test result of the scaffold obtained in Example 1. The results show that the overall porosity of the scaffolds of different components is about 60%, maintaining good consistency, indicating that the 3D printed scaffold is reliable and stable. At the same time, the high porosity can also promote the continuous growth of cells.
[0039] Figure 1 (e) is the compressive strength test result of the stent obtained in Example 1. The results show that after adding titanium dioxide powder, the compressive strength of the stent increases significantly. The compressive strength of the CS stent is 5.72Mpa, and after adding titanium dioxide powder, the compressive strength increases to more than 20Mpa.
[0040] Figure 1 (f) is the 21-day degradation test result of the stent obtained in Example 1. It can be seen that the degradation rate of the CS stent is faster, reaching 11.1% ( Figure 1 f). This shows that the addition of titanium dioxide can effectively improve the mechanical properties of the scaffold and slow down the degradation rate of the scaffold, which better matches the speed of bone regeneration.
[0041] Experimental Example 2 Effect of bone repair scaffold on BMSCs cells
[0042] Experimental method: Cell culture: BMSCs were cultured in DMEM supplemented with 10% FBS, 100 U / ml penicillin and 100 mg / ml streptomycin in an incubator at 37°C, 95% humidity and 5% CO2.
[0043] Cell proliferation: BMSCs cells were cultured at 2×10 3 The cells were seeded at a high density in a 96-well plate, and the culture medium was replaced every other day. The cell viability and proliferation capacity were evaluated using the CCK8 detection kit after adding the ion extract for 1, 3, and 5 days of co-culture. After adding CCK8 to each well, the cells were incubated in the incubator in the dark for 1 hour and then taken out. The absorbance of the samples was measured at a wavelength of 450 nm using an ELISA reader.
[0044] Cell migration: BMSCs cells were cultured at 4 × 10 5 The cells were inoculated with a certain amount of cells and cultured in an incubator at 37°C, 5% CO2, and 95% humidity for 24 hours. Then, a straight "scratch" was made with a p200 pipette tip, and the original state of the "scratch" was recorded. Then, complete culture medium prepared with ion extract was added and cultured for 24 hours. The final state was recorded after washing with FBS. ImageJ was then used to obtain the original (A0) and final (Af) area of the "scratch". The migration rate was calculated using the following formula: S = (A0-Af) / A0×100%
[0045] Cell live and dead fluorescence staining: Calcein AM / PI was used to observe the growth activity of cells. After Calcein AM enters the cells, live cells containing esterase can produce Calcein, while dead cells can hardly produce it, so only live cells will show green fluorescence. The disordered area of the dead cell membrane only allows the propidium iodide (PI) solution to pass through and reach the cell nucleus, thereby embedding its DNA double helix and producing red fluorescence. 2×10 3 The cells were seeded in 96-well plates and photographed using an inverted fluorescence microscope after five days of culture.
[0046] The experimental results are as follows Figure 2 As shown, where:
[0047] Figure 2 (a)(b) are the proliferation of BMSCs (Relative proliferation, Cell viability) after 1, 3, and 5 days of culture. The results show that the prepared scaffolds had no toxic side effects during the 5-day culture period, and the activity of BMSCs in the CST9:1 group was significantly higher than that in other control groups ( Figure 2 a).
[0048] Figure 2 (c) is an image of cell migration after 24 hours of culture. The speed and coverage area of cells growing from outside the scratch to the scratch area reflect the migration ability of cells. The image shows that the CST9:1 group has a more obvious growth trend toward the center and a larger growth area. Figure 2 (e) is the quantitative analysis image of cell migration rate after 24 hours of culture. The results show that the cell migration rate of BMSCs in the CST9:1 group was 27.91±2.77%, which was higher than that of the blank control group (17.61±1.66%) and the CS group (22.85±1.29%).
[0049] Figure 2 (d) Live-dead staining was used to determine the liveness and deadness of BMSCs. AM was used to determine the live cells (shown in green) and PI was used to determine the dead cells (shown in red). The dead-live staining results showed that after 5 days of culture, the proportion of live cells in the CST9:1 group was higher than that in the other groups, indicating that the CST9:1 group could improve the cell viability of BMSCs ( Figure 2 d); The above results can be analyzed to conclude that CST9:1 group is the best embodiment of this application.
[0050] Thus, through in vitro biological experiments, the present invention provides a method for preparing a bone repair scaffold, which is manufactured by combining calcium silicate with titanium dioxide, which reduces the degradation rate of the scaffold to a limited extent and improves the mechanical stability. It also has good cell compatibility and can promote cell proliferation. The present invention provides a new strategy for treating bone defects and can also provide new ideas for personalized clinical treatment.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a bone repair scaffold, characterized in that: The steps include: Mixing calcium silicate powder and titanium dioxide powder to obtain a mixed powder; Adding photosensitive resin to the mixed powder to obtain printing slurry; The printing slurry is 3D printed to obtain a printing bracket; The printed scaffold is sintered to obtain a bone repair scaffold.
2. The preparation method according to claim 1, characterized in that: The added amount of the titanium dioxide powder accounts for ≤50% of the total mass of the mixed powder.
3. The preparation method according to claim 2, characterized in that: The added amount of the titanium dioxide powder accounts for 10% of the total mass of the mixed powder.
4. The preparation method according to claim 1, characterized in that: The added amount of the mixed powder is such that the solid content in the printing slurry is 30%-40%.
5. The preparation method according to claim 1, characterized in that: The sintering temperature is 1100° C.-1200° C., and the sintering time is 3 h-4 h.
6. The preparation method according to claim 4, characterized in that: After the sintering is completed, a drying step is further included, and the drying temperature is 50°C-60°C.
7. A bone repair scaffold prepared according to any one of the preparation methods of claims 1-6.
8. Use of the bone repair scaffold according to claim 7 in the preparation of bone defect repair materials.
Citation Information
Patent Citations
Black bioglass as well as preparation method and application thereof
CN109336381A
Bioactive 3D printing ceramic and preparation method thereof
CN112408968A
Disordered porous biological ceramic scaffold based on photocuring three-dimensional printing as well as preparation method and application of disordered porous biological ceramic scaffold
CN112898011A
Improvements in and relating to ceramic materials
GB505165A
Device and method for setting coordinate system of total knee arthroplasty
KR1020240126629A